Estimativa da diversidade genética e análise da estrutura de populações de espécies de Conyza - Marochio, Carlos Alexandre (2014)
The purpose of this study was to investigate the genetic variability at the molecular level, and check how they are genetically structured species Conyza canadensis, C. bonariensis and C. sumatrensis, analyzing polymorphism loci in simple sequence repeat (SSR loci) of DNA, also called microsatellite loci. Samples of C. canadensis were analyzed, sensitive and resistant to glyphosate, and C. bonariensis resistant and dual resistance, collected in the Central Valley of Califomia (USA), and samples of C. sumatrensis sensitive and resistant collected in six counties of the State of Parana (Brazil), using the HWO2, HW06, HW07, HW09, HWI4, HW29, HWSSROl, HWSSRO3, HWSSRO4, HWSSRO7, HWSSRO9 and HWSSRll primers to analyze the polymorphism in 12 loci microsatellites. The large number of alleles (26) was found in C. sumatrensis. The largest proportion of polymorphic microsatellite loci (9l.67%) was observed in the plants of the species C. bonariensis, but the number of alleles per locus (Na = 2.l667), effective number of alleles (Ne = l.9388), and mean expected heterozygosity (He - ().429l) was also higher in samples of C. sumatrensis, indicating that the genetic diversity in the species is longer C. sumatrensis. Samples of C. canadensis showed the lowest genetic diversity. The genetic divergence between the three species of Conyza was high (FST = 0.25), indicating that these populations are genetically structured. The HW07, HWI4, HW29, HWSSR0l, HWSSR03, HWSSR04, HWSSRO7, HWSSRO9 and HWSSRll primers were shown to differentiate the three species of Conyza. The proportion of polymorphic microsatellite loci was higher in the samples of C. canadensis resistant (R), but the effective number of alleles and the values of Ho and He, were equivalent in sensitive genotypes (S) and resistant, indicating that C. canadensis-S and C. canadensis-R has the same potential to colonize new areas. The values of Ho and He were also similar among the genotypes of C. sumatrensis-S and C. sumatrensis-R. Samples of C. sumatrensis formed genetically structured populations (FST = 0.4822). In the municipalities of Campo Mourão and Cafelândia copies of Conyza features at the molecular level, for microsatellite loci C. canadensis, C. bonariensis and C. surnatrensis, and copies that share alleles characteristic of the species, indicating the occurrence of the three species, suggesting that there is an exchange of alleles between the three Conyza species in that region.